Spontaneous Secretion of the Citrullination Enzyme PAD2 and Cell Surface Exposure of PAD4 by Neutrophils - Zhou, Yebin; Chen, Bo; Mittereder, Nanette; Chaerkady, Raghothama; Strain, Martin; An, Ling-Ling; Rahman, Saifur; Ma, Wenting; Low, Choon Pei; Chan, Denice; Neal, Frances; Bingham, Clifton O.; et al. (Frontiers in Immunology, 2017)
Autoantibodies directed against citrullinated epitopes of proteins are highly diagnostic of rheumatoid arthritis (RA), and elevated levels of protein citrullination can be found in the joints of patients with RA. Calcium-dependent peptidyl-arginine deiminases (PAD) are the enzymes responsible for citrullination. PAD2 and PAD4 are enriched in neutrophils and likely drive citrullination under inflammatory conditions. PADs may be released during NETosis or cell death, but the mechanisms responsible for PAD activity under physiological conditions have not been fully elucidated. To understand how PADs citrullinate extracellular proteins we investigated the cellular localization and activity of PAD2 and PAD4, and we report and we report that viable neutrophils from healthy donors have active PAD4 exposed on their surface and spontaneously secrete PAD2. Neutrophil activation by some stimulatory agents increased the levels of immunoreactive PAD4 on the cell surface, and some stimuli reduced PAD2 secretion. Our data indicate that live neutrophils have the inherent capacity to express active extracellular PADs. These novel pathways are distinguished from intracellular PAD activation during NETosis and calcium influx mediated hypercitrullination. Our study implies that extracellular PADs may have a physiological role under non-pathogenic conditions as well as a pathological role in RA.